Density Functional Theory Calculation of Adsorption of NaCl on Chlorophyll - Rosli, Ahmad Nazrul; Ahmad Zabidi, Noriza; Abu Kassim, Hasan; Hj Mohd Arof, Abdul Kariem; Shrivastava, Keshav N. (Malaysian Journal of Science, 2009)
We have calculated the vibrational frequencies of chlorophyll-a, chlorophyll-a + 1 NaCl and chlorophyll-a + 2 NaCl from the first principle. We are able to find the vibrational frequencies as well as the structural parameters in all of the three cases. The Mg atoms are found to absorb Na atoms which distort the structure. The vibrational frequencies calculated for the chlorophyll-a are in reasonable agreement with those found from the Raman Spectra.